Ethanol extract of Polygonatum cyrtonema Hua mitigates non-alcoholic steatohepatitis in mice - Chen, Dongliang; Shen, Yue; Huang, Fang; Huang, Bo; Xu, Shangfu; Li, Lisheng; Liu, Jie; Li, Zheng; Li, Xia (Frontiers in Pharmacology, 2025)
BackgroundPolygonum cyrtonema Hua is a kind of traditional Chinese botanic drug. Modern pharmacological research has confirmed that Polygonum cyrtonema Hua is able to alleviate nonalcoholic fatty liver disease, but the precise mechanism requires further investigation. This study investigated the protective effects and underlying mechanisms of Polygonatum cyrtonema ethanol extract (PCE) against Non-alcoholic steatohepatitis (NASH) in mice.MethodsUHPLC-MS/MS was utilized to analyze the metabolites of PCE. The NASH mouse model was establishment in C57BL/6J mice via high-fat diet (HFD) feeding for 12 weeks, and from the 9th week, mice were gavaged with PCE (100, 300, and 900 mg/kg/day), simvastatin (4 mg/kg) or saline. One hand, liver injury was assessed by serum enzymes, biochemistry, and histopathology; On the other hand, RNA-seq, qPCR, and Western blot were employed to investigate the related molecular mechanisms.Results211 metabolites were identified through UHPLC-MS/MS analysis. PCE ameliorated HFD induced liver injury and improved hepatocellular degeneration and steatosis in a dose-dependent way. PCE restored the expression of AMPK, SIRT1, SREBP1 and PPAR-α both in mRNA and protein levels. RNAseq identified unique gene expression profiles in response to high-fat diet (HFD) compared to the PCE treatments. HFD-induced DEGs were attenuated or abolished following PCE treatments. Ingenuity pathway analysis of RNA-seq data revealed key canonical pathways and upstream molecules regulated by PCE.ConclusionOur findings confirm the ability of PCE in alleviating NASH and underscores AMPK/SIRT1 pathway as a potential theraputic target for NASH treatment.